(untitled) (Bangladesh Journal of Public Administration, 2022)
The study’s objectives were to describe some selected characteristics of the dairy farmers, determine the extent of covid-19 effects on dairy farmers’ livelihoods, and identify the factors that influence covid-19 effect on dairy farmers’ livelihoods. In Pungali union, Faridpur Upazila, Pabna district, 95 dairy farmers were randomly chosen to participate in the study. In order to gather data from the respondents in May 2022, a pre-tested interview schedule was implemented. The study’s independent variables were nine specifically chosen characteristics of the respondents, whereas the dependent variable was the effects of COVID-19 on the livelihoods of dairy farmers. The interview survey revealed that the highest proportion (91.6 percent) of the respondents explained that covid-19 significantly affected dairy farmers’ livelihoods. In comparison, 8.4 percent of farmers explained that covid-19 did not affect dairy farmers’ livelihoods. Among selected characteristics of the respondents, viz., the problem faced in the covid-19 situation and contact with communication media significantly contributed significantly to their covid-19 effects on dairy farmers’ livelihoods. Therefore, to lessen the consequences of COVID-19 on the livelihoods of dairy farmers, policymakers should take these critical issues into account.